Local Government Strategy in Empowering Tourism Villages - Hana Ihat Nurfadlilah (Wadah Inovasi Indonesia, 2023)
A tourism village is a rural area that has a special allure and is able to bring visits to tourists where more specifically a tourist village is bound by strong cultural values ​​and traditional characteristics. When a village has been agreed upon, proclaimed as a